2016
DOI: 10.1002/2016jd025501
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of streamflow simulation results of land surface models in GLDAS on the Tibetan plateau

Abstract: The Global Land Data Assimilation System (GLDAS) project estimates long‐term runoff based on land surface models (LSMs) and provides a potential way to solve the issue of nonexistent streamflow data in gauge‐sparse regions such as the Tibetan Plateau (TP). However, the reliability of GLDAS runoff data must be validated before being practically applied. In this study, the streamflows simulated by four LSMs (CLM, Noah, VIC, and Mosaic) in GLDAS coupled with a river routing model are evaluated against observed st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 106 publications
0
39
1
1
Order By: Relevance
“…The NSE values range from 0.70 to 0.89 at Yellow River stations, which are better than previous works where NSE values range from 0.49 to 0.85 based on GLDAS1/Variable Infiltration Capacity simulations (Cuo et al, ) and 0.31 to 0.89 based on GLDAS1/Noah simulations (Zheng et al, ). Bai et al () also evaluated streamflow simulations of GLDAS1 over the TP, and their results showed that Kling‐Gupta efficiency values vary from −0.75 to 0.09 at the TNH and ZMD stations, which are much lower than those from CSSPv2 simulations (Table ). In short, the CSSPv2 model reasonably simulated monthly streamflow over the Sanjiangyuan region and outperformed many other land surface hydrological models in the literature.…”
Section: Validation Of Csspv2 Over the Sanjiangyuan Regionmentioning
confidence: 99%
“…The NSE values range from 0.70 to 0.89 at Yellow River stations, which are better than previous works where NSE values range from 0.49 to 0.85 based on GLDAS1/Variable Infiltration Capacity simulations (Cuo et al, ) and 0.31 to 0.89 based on GLDAS1/Noah simulations (Zheng et al, ). Bai et al () also evaluated streamflow simulations of GLDAS1 over the TP, and their results showed that Kling‐Gupta efficiency values vary from −0.75 to 0.09 at the TNH and ZMD stations, which are much lower than those from CSSPv2 simulations (Table ). In short, the CSSPv2 model reasonably simulated monthly streamflow over the Sanjiangyuan region and outperformed many other land surface hydrological models in the literature.…”
Section: Validation Of Csspv2 Over the Sanjiangyuan Regionmentioning
confidence: 99%
“…In particular, it is well known that land surface models have some difficulties (e.g. parameter tuning in boundary layer schemes) when applying to the TP, even though they sometimes have good performances in different regions or basins (Xia et al, 2012;Bai et al, 2016). For example, Xue et al (2013) indicated that GNoah_E underestimated ET wb in the upper Yellow River and Yangtze River basins on the Tibetan Plateau, mainly due to its negative-biased precipitation forcing.…”
Section: Uncertaintiesmentioning
confidence: 99%
“…For example, and Liu et al (2016a) evaluated multiple ET estimates against the water balance method on annual and monthly timescales. Bai et al (2016) assessed streamflow simulations of GLDAS LSMs in five major rivers over the TP based on the discharge observations. Although uncertainties might exist among different datasets with various spatial and temporal resolutions which are calculated using different algorithms (Xia et al, 2012), they offer an opportunity to examine the general basin-wide water budgets and their uncertainties in gauge-sparse regions such as the TP considered in this study.…”
mentioning
confidence: 99%
“…The TP, known as the "third pole", has an average elevation of over 4000 m above sea level (a.s.l) [42]. The TP is also the source of many Asian rivers, such as the Yellow River, the Yangtze River, and the Mekong River, supporting hundreds of millions of people living downstream [43]. Owing to the sparse population, the existing rain gauge networks over the TP are extremely sparse (see Figure 1 in Section 2.1), which is challenging for hydrological research and practices.…”
Section: Introductionmentioning
confidence: 99%